Manfaat Literasi Digital Generasi Z sebagai Preferensi Tujuan Wisata dan Promosi Pariwisata - Viona Amelia; Danang Prasetyo (Ideas Publishing, 2023)
Generation Z activities in the realm of digital technology extend to the preference of tourist destinations to be visited. This study aims to determine surfing activities in cyberspace carried out by students which are closely related to the decision to take a tour and the actions afterward. Descriptive qualitative research method with purposive sampling technique on 407 respondents. The results of the study show that digital literacy among students at Tourism Campus is high, they are able to make the final decision to visit a destination based on considerations obtained from surfing results in cyberspace. The decision to visit a tourist destination is not only as a user, but also involved in promoting it.